solve this system of equations 4x^2-5xy-y^2=10 2y=1-5x

Question

Asked 9/20/2009 3:53:33 PM

Updated 356 days ago|12/19/2022 2:33:46 PM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Expert answered|Heather71|Points 1210|

Question

Asked 9/20/2009 3:53:33 PM

Updated 356 days ago|12/19/2022 2:33:46 PM

1 Answer/Comment

Rating

3

4x^2-5xy-y^2=10

2y=1-5x

Y=(1-5X)/2

NOW REPLACE Y IN THE FIRST EQUATION WITH (1-5X)/2

4X^2-5X(1-5X)/2-[(1-5X)/2]^2=10

4X^2-(5X-25X^2)/2-(1-10X+25X^2)/4=10 THE COMMON DENOMINATOR IS 4 FOR THE LEFT SIDE.

(16X^2-10X+50X^2-1+10X-25X^2)/4=10

-41X-1=10*4

-41X=40+1

X=41/-41

X=-1 ANS.

Y=(1-5*-1)/2

Y=(1+5)/2

Y=6/2

Y=3 ANS.

PROOF:

4*-1^2-5*-1*3-3^2=10

4*1+15+-9=10

4+15-9=10

10=10

2y=1-5x

Y=(1-5X)/2

NOW REPLACE Y IN THE FIRST EQUATION WITH (1-5X)/2

4X^2-5X(1-5X)/2-[(1-5X)/2]^2=10

4X^2-(5X-25X^2)/2-(1-10X+25X^2)/4=10 THE COMMON DENOMINATOR IS 4 FOR THE LEFT SIDE.

(16X^2-10X+50X^2-1+10X-25X^2)/4=10

-41X-1=10*4

-41X=40+1

X=41/-41

X=-1 ANS.

Y=(1-5*-1)/2

Y=(1+5)/2

Y=6/2

Y=3 ANS.

PROOF:

4*-1^2-5*-1*3-3^2=10

4*1+15+-9=10

4+15-9=10

10=10

Added 356 days ago|12/19/2022 2:33:46 PM

This answer has been confirmed as correct and helpful.

38,690,002

questions answered

There are no comments.